The Role of Islamic Education Teachers in Shaping Student Character in the Era of Society 5.0 - Nuriyati, Tuti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Character development in children is a crucial aspect that underscores the significant role of teachers. In addition to being educators, teachers must also guide and serve as role models for their students. This study highlights the important role of teachers in shaping students' morals in the Society 5.0 era. The primary objective of this research is to understand how students' morals change in the context of Society 5.0 and the role of teachers in fostering better and more character-driven students. The study employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews and observations to achieve accurate and comprehensive results. The findings indicate that the moral condition of students at Madrasah Tsanawiyah Negeri 1 Bengkalis is generally good. The role of teachers in shaping students' morals in the Society 5.0 era can be divided into three stages: 1). Before the Learning Process: Teachers function as instructional designers, role models, and parental figures. 2). During the Learning Process: Teachers act as organizers, motivators, facilitators, innovators, and mentors. 3). After the Learning Process: Teachers serve as supervisors and evaluators.This research provides insights into how teachers can adapt and innovate in the digital era to enhance students' morals and character, offering practical recommendations for future educational development.